DIVERSIFICATION OF HERBAL PRODUCTS BASED ON LOCAL WISDOM AS AN EFFORT TO PREVENT STUNTING FOR THE COMMUNITY OF OLAK KEMANG VILLAGE - Kasmadi, Fathnur Sani; Maharini, Indri; Maimum, Maimum; Fitrianingsih, Fitrianingsih; Neldi, Vina; Astuti, Novia Tri; Perawati, Santi; Yuliawati, Yuliawati; Yuliandani, Yuliandani; Nurfadilah, Nurfadilah (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Stunting, or chronic malnutrition, remains a significant public health challenge in Indonesia, impacting the cognitive and physical development of children. This community service project aimed to address this issue through a culturally sensitive and sustainable approach in the community of Olak Kemang Village, Jambi. The program focused on diversifying local wisdom-based herbal products to improve nutritional intake among pregnant women, lactating mothers, and children under five. The method involved a three-stage process: (1) socialization and nutritional education about stunting, (2) training on the hygienic processing of local plants rich in micronutrients, such as Moringa (Moringa oleifera) and Katuk leaves (Sauropus androgynus), and (3) a hands-on workshop on creating diversified, child-friendly products like herbal powders, fortified cookies, and puddings. Pre- and post-activity questionnaires demonstrated a significant increase in participants' knowledge and awareness of stunting prevention, from 67,4% to 90,58%. Participants also successfully produced several innovative herbal food products. This initiative highlights that empowering communities by integrating local knowledge with scientific principles is a promising and effective strategy for stunting prevention. Keywords: Stunting, community service, herbal product, nutrition, local wisdom.